Assessment of Social Sustainability Using Social Society Index: A Clustering Application - SELAM, AYŞE AYÇİM; ARIOĞLU, MAHMURE ÖVÜL (EUROPEAN CENTER SUSTAINABLE DEVELOPMENT, 2018)
With the massive economic development and vast environmental degradation over the last decade, sustainability and sustainable development have become primary concepts in governments. agenda. Sustainability has three pillars, namely environmental, economic and social, the latter gaining attention relatively later than the others. Some organizations evaluate the world countries for social sustainability using indices such as the Organisation for Economic Co-operation and Development (OECD) Better Life Index, Human Development Index and Social Society Index (SSI). SSI is used to rank world countries and evaluate their level of sustainability. SSI is a scoring system developed by Social Society Foundation to measure human wellbeing, environmental wellbeing and economic wellbeing every 2 years. In the evaluation process, SSI calculates scores using 21 indicators and publishes the actual situation on sustainability, progress over time and differences in development per region and per income class. In this paper, human wellbeing indicators of SSI are used to cluster world countries with k-means algorithm to assess social sustainability. Human wellbeing indicators are grouped into basic needs, personal development and health, and well-balanced society, all of which are measured with 3 indicators. The clusters obtained are compared with SSI rankings and the results are elaborated.
Keywords: Social Sustainability; Social Society Index; Clustering; k-means algorithm